Diagnostic biopsy of sentinel lymph nodes in mammary gland cancer - R. P. Nikitenko; E. A. Koichev; S. P. Degtyarenko (Клінічна хірургія)
Objective.To improve the diagnostic biopsy of sentinel lymph nodes in patients, suffering mammary gland cancer, using fluorescent lymphography, and to reduce the quantity of postoperative complications.